ANALISIS LAYANAN PURNA JUAL AUTO 2000 BANDAR LAMPUNG - Arif Pramono (GEMA : Jurnal Gentiaras Manajemen dan Akuntansi, 2013)
The key to keep customers loyal is the company must give satisfaction to its customers.Satisfaction can be achieved through the provision of optimum service to customers, for examplethrough the provision of prompt delivery so that customers do not have to wait too long, providingengine maintenance suggestions to customers.From the data analysis and testing hypotheses about the analysis of the influence of aftersales services to customer loyalty in the division after sales AUTO 2000 Bandar Lampungconclusion: The magnitude of the effect relationship sales services to customer loyalty in the divisionafter sales AUTO 2000 Bandar Lampung Raden Intan is 0.739. While the magnitude of effect of theinfluence of after-sales services to customer loyalty can be seen from the magnitude of thecoefficient of multiple determination (R2) of 0.546, which means 54.6% of the effect of customerloyalty on the division after sales AUTO 2000 Bandar Lampung Raden Intan effected by variablescan influence sales service selling.Results of hypothesis testing and calculation of the discussion can be concluded that theafter-sales service have an influence on consumer loyalty in the division after sales AUTO 2000Bandar Lampung. Where t count> t table or statistical 10.854 t count> t table statistic of 1.66 meansthat Ho is rejected and Ha accepted. means that there are significant between-sales services tocustomer loyalty in the division after sales AUTO 2000 Bandar Lampung.